Security Risk Evaluation of ZombAI Claude: Prompt Injection as a Backdoor for Command and Control Exploits - Indra Bayu; Mahar Faiqurahman (ISB Atma Luhur, 2026)
The rapid adoption of AI in industrial automation has introduced AI agents functioning as Command and Control (C2) systems capable of managing infrastructure autonomously. The integration of